2015
DOI: 10.1021/es506274x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Marine and Terrestrially Derived Dissolved Organic Matter on Mercury Speciation and Bioavailability in Seawater

Abstract: Methylmercury (MeHg) is the only species of mercury (Hg) to biomagnify in aquatic food-webs to levels that are a widespread concern for human and ecological health. Here we investigate the association between dissolved organic matter (DOM) in seawater and Hg speciation and uptake using experimental data and field measurements from Long Island Sound (LIS) and the Northwestern Atlantic continental margin. We measured differences in DOM composition across sampling stations using excitation emission matrix fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 71 publications
5
91
0
Order By: Relevance
“…This is probably due to the fact that the DGM and THg concentrations in the nearshore area were all higher than those in the open sea. This distribution pattern of %DGM was consistent with the results of previous studies (Baeyens and Leermakers, 1998;Schartup et al, 2015;Soerensen et al, 2013). In addition, we found that %DGM at the coastal stations of the Zhoushan Island was lower than those other stations.…”
supporting
confidence: 92%
“…This is probably due to the fact that the DGM and THg concentrations in the nearshore area were all higher than those in the open sea. This distribution pattern of %DGM was consistent with the results of previous studies (Baeyens and Leermakers, 1998;Schartup et al, 2015;Soerensen et al, 2013). In addition, we found that %DGM at the coastal stations of the Zhoushan Island was lower than those other stations.…”
supporting
confidence: 92%
“…This is consistent with previous studies suggesting an enhanced Hg methylation under low sulfidic (Graham et al, 2012a) or low DOC conditions (French et al, 2014). Thus, the effect of DOM on Hg uptake and methylation by microbes may strongly depend on environmental conditions (Schartup et al, 2015). Here, the reason why the same amount of amended rice straw resulted in a different DOC increase in the two soils may be related to the microbial community that degraded rice straw.…”
Section: Discussionsupporting
confidence: 92%
“…These values were significantly lower than those in open oceans (~10-50 %, e.g., Mason et al 2001;Soerensen et al 2013;Schartup et al 2015) and comparable to concentrations of many coast and offshore environments (1-5 %, e.g., Ci et al 2011a, d). It should be noted that our values were slightly higher than those in the northern SCS in the summer cruise (3.0 %, Fu et al 2010) but significantly higher than those in the winter in the SEATS (~1 %) and other seasons (1-1.6 %) (Tseng et al 2013).…”
Section: Hg(0) In Watermentioning
confidence: 58%
“…Many field measurements also widely reported that the water Hg(0) concentrations in nearshore environments were generally higher than those in the open water (e.g., Mason et al 2001;Ci et al 2011d). The field observations and incubation experiments suggest that the special properties of nearshore environment, such as the enhanced THg levels, the estuarine mixing, and the high biological activity, can either promote the production of water Hg(0) and/or increase the Hg(0) input to the coastal water (Amyot et al 1997;Lanzillotta et al 2002;Rolfhus et al 2003;Covelli et al 2008;Fantozzi et al 2009;Schartup et al 2015;Ci et al 2016).…”
Section: Hg(0) In Watermentioning
confidence: 99%
See 1 more Smart Citation